Cholesteryl ester transfer protein inhibitors for dyslipidemia: focus on dalcetrapib - Goldberg AS; Hegele RA (Dove Medical Press, 2012)
Alyse S Goldberg, Robert A HegeleDepartment of Medicine, Schulich School of Medicine and Dentistry, Western University, London, Ontario, CanadaAbstract: Among the noteworthy recent stories in the management and prevention of atherosclerotic cardiovascular disease (CVD) is the saga of the development of pharmacological inhibitors of cholesteryl ester transfer protein (CETP). Inhibiting CETP significantly raises plasma concentrations of high-density lipoprotein cholesterol, which has long been considered a marker of reduced CVD risk. However, the first CETP inhibitor, torcetrapib, showed a surprising increase in CVD events, despite a dramatic increase in high-density lipoprotein cholesterol levels. This paradox was explained by putative off-target effects not related to CETP inhibition that were specific to torcetrapib. Subsequently, three newer CETP inhibitors, namely dalcetrapib, anacetrapib, and evacetrapib, were at various phases of clinical development in 2012. Each of these had encouraging biochemical efficacy and safety profiles. Dalcetrapib even had human arterial imaging results that tended to look favorable. However, the dalcetrapib development program was recently terminated, presumably because interim analysis of a large CVD outcome trial indicated no benefit. These events raise important questions regarding the validity of the mechanism of CETP inhibition and the broader issue of whether pharmacological raising of high-density lipoprotein cholesterol itself is a useful strategy for CVD risk reduction.Keywords: dalcetrapib, CETP inhbitor, HDL, cardiovascular disease